IV/IT hUC-MSCs Infusion in RRMS and NMO: A 10-Year Follow-Up Study - Lu, Zhengjuan; Zhu, Lin; Liu, Zhuo; Wu, Jiayong; Xu, Yun; Zhang, Cun-Jin (Frontiers in Neurology, 2020)
Background: Stem cells transplantation is emerging as a potential therapeutic strategy in several autoimmune diseases. However, the safety and feasibility of long-term combined intravenous (IV) and intrathecal (IT) administration of hUC-MSCs in Relapse Remitting MS (TTMS) and Neuromyelitis Optica (NMO) is largely unknown. Objectives: In this study, we followed-up the long-term safety and feasibility of combined intravenous and intrathecal human umbilical cord mesenchymal stem cells (UC-MSCs) transplantation in patients with RRMS and NMO. Methods: 5 NMO patients and 5 RRMS patients treated intravenously (4 times) and intrathecally (3 times) over a 21-day period with low-dose allogeneic umbilical cord blood derived mesenchymal stem cells (MSC). All of the patients were monitored regularly by an investigator in a blinded manner to access the Expanded Disability Status Scale (EDSS), magnetic resonance imaging (MRI) characteristics, and adverse events every 3 months within 12 months and once every year thereafter for 10 years after transplantation. Results: During the long-term follow-up, our data suggested that combined intravenous (IV) and intrathecal (IT) administration of hUC-MSCs transplantation is safe and feasible. None of any intolerant adverse events, such as tumor formation and peripheral organ/tissue disorders, were observed throughout the 10-year follow-up. Conclusions: These data suggests that combined intravenous and intrathecal low-dose UC-MSCs transplantation is safe and feasible in RRMS and NMO patients in long-term. The conclusion requires confirmation by future clinical trials in larger cohort.